Implementation Of Online Passport Making Policy In Creating Good Governance At Tpi Cirebon Class I Immigration Office - Insan Kholis; Awaludin Putra Hertiansyah; Hery Nariyah; Moh. Sutarjo (Journal of Social Research, 2024)
E-Passport has not achieved its goal of making passport services faster, clearer and more accountable since its launch as a public service. As a result, people have to come back repeatedly to get access to the app. This study investigates the use of e-government at the TPI Cirebon Class I Immigration Office. The aim is to find out how to use "Implementation of the Online Passport Creation policy in creating good governance at the TPI Cirebon Class I Immigration Office" and what efforts are being made by the TPI Cirebon Class I Immigration Office to overcome existing obstacles. This case study uses a qualitative study methodology descriptive. The purposive sampling method was used to select informants. Information was collected through interviews, documentation, and literature and field research. The UNDP theory uses nine components. The research results show that the system for making passports via the internet at the TPI Cirebon Class I Immigration Office has been running well and transparently in improving the quality of government. However, several supporting components are not yet perfect.